PENDIDIKAN KARAKTER PADA MATERI PERKULIAHAN SIKAP ILMIAH UNTUK MAHASISWA PENDIDIKAN IPA INSTITUT PENDIDIKAN NUSANTARA GLOBAL - Mulia Rasyidi (Pusat Riset dan Inovasi Nasional, 2022)
This research has a background problem of the low character values seen in students of the Global Nusantara Education Institute of the Science Education Study Program when learning science in scientific attitude lectures. So far, the learning of scientific attitude course material emphasizes the cognitive aspect and has not promoted the importance of inculcating character values in learning. Changes in teaching point of view are considered necessary where there is a need for alignment between mastery of concepts and improvement of character. The purpose of this study is to explain the learning tools, the application of learning, the advantages and disadvantages of the character education learning system when learning science in scientific attitude lecture material. This research was carried out at the Global Nusantara Education Institute for the Science Education Study Program, with the research subjects being students of the second semester of the Science Education Study Program for the Academic Year 2020/2021. This type of research is descriptive research using a quantitative approach. The results of the study obtained that the RPS suitability reached 91.06%. This means that it has shown the planting of character values in the elements that make up the RPS. In addition, from the results of the questionnaire analysis, the percentage of success in planting character education in students reached 81.27%. This indicates that after the science learning process, character education has a positive effect on students' personal development, it can be seen that the character values of each student can be seen very well.